STUDENTS’ PERCEPTIONS AND ATTITUDES TOWARDS THE USE OF INSTAGRAM IN ENGLISH LANGUAGE WRITING (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ This study examines university studentsâ€™ perceptions and attitudes towards the use of Instagram in English language writing. Like other social networking sites (SNS), the design of Instagram promotes community-centeredness, and supports the dissemination of authentic content that creates opportunities for meaningful interactions among language learners.Methodology â€“ There were 101 participants of this study who participated in a descriptive English essay writing activity on Instagram, answered a set of questionnaire with 20 closed-ended items, and five open-ended questions about using Instagram for English language learning. Focus groupsâ€™ discussions with all of the respondents were held to elaborate the open-ended items. The closed-items were analysed quantitatively using mean scores, while the open-ended items were analysed both quantitatively (mean scores) and qualitatively (content analysis).Findings â€“ The results demonstrated studentsâ€™ high positive perceptions and views towards using Instagram in improving their writing skills, but moderate attitudes.Significance â€“ Based on the more favourable responses, it is about time that language teachers implement the preeminent social media platform such as Instagram to create conducive learning environment that could boost studentsâ€™ motivation in English language learning.